Downregulation of NF-κB activation pathways using essential oil derived from Citrus pseudolimon: Anticancer and anti-inflammatory potential. (January 2023) - Sajid, Arfaa; Manzoor, Qaisar; Sajid, Anam; Nazir, Arif; Mumtaz, Muhammad Arsalan; Fatima, Najum; Alshawwa, Samar Zuhair; Iqbal, Munawar; Younas, Umer
Abstract: This study focuses on isolating and characterizing the essential oil obtained from Citrus pseudolimon ( C. pseudolimon ) fruit peel for inhibition of cancer and inflammation through the downregulation of nuclear factor-kappa B (NF-κB) activation pathways. C. pseudolimon essential oil (CPEO) was isolated through steam-hydro distillation and characterized through GC-MS. The 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2H-tetrazolium bromide (MTT) assay was performed to evaluate its anticancer potential against colon, leukemia, multiple myeloma, pancreatic, lung, and squamous carcinoma cells. The expression of proteins involved in cell proliferation like Cyclin E1 and intercellular adhesion molecule 1 (ICAM-1), anti-apoptotic proteins i.e. X-linked inhibitor of apoptosis protein (XIAP), capsapse-3, and poly-ADP ribose polymerase (PARP) was studied through western blotting analysis. The constituents were separated and limonene, limonene oxide, α-pinene, mentha-6, 8-diene, 2-hydroperoxide, cis -carveol, and β-Myrcene were the major ones. CPEO exhibited a dose-dependent inhibition of cell proliferation up to 83–98% for 100 μg/mL oil. Flow cytometry analysis revealed that CPEO treatment in cancer cells induced a decrease in DNA contents in the synthesis (S-phase) of the cell cycle. Furthermore, CPEO downregulates the NF-κB; an inflammatory transcription marker and repressed the expression of genes regulated by NF-κB like Cyclin E1, ICAM-1, and XIAP responsible for cell proliferation and anti-apoptosis. Results revealed that CPEO adopt various mechanisms and routes like arresting of S-phase in cell cycle, induction of apoptosis, anti-inflammatory and anti-metastatic activities to induce death in cancer cells. The auspicious and persuasive bioactivities of CPEO showed that it might be very effective herbal medicine against this deadly disease. Highlights: Isolation of essential oil from C. pseudolimon fruit peel for inhibition of cancer. CPEO was isolated through steam-hydro distillation. CPEO downregulates the NF-κB an inflammatory transcription marker. CPEO inhibited induction of apoptosis, anti-inflammatory and anti-metastatic activities. Bioactivities of CPEO proposed it as an effective herbal medicine against cancer.